Gut metabolomics and 16S rRNA sequencing analysis of the effects of arecoline on non-alcoholic fatty liver disease in rats - Zhu, Lingping; Li, Duo; Yang, Xuefeng (Frontiers in Pharmacology, 2023)
Non-alcoholic fatty liver disease (NAFLD) is gradually increasing in prevalence as the primary cause of fatty liver disease. Betel nut has been used for the treatment of gastrointestinal diseases. In this study, we analyzed the pathology, serology, gut flora, and metabolites in a rat model of NAFLD with and without betel nut alkaloid treatment using an integrated approach involving pathology, serological testing, 16S rRNA gene sequencing, and ultra-performance liquid chromatography-mass spectrometry metabolomics. 2 rats were used for validation of the model. Then, 30 SD rats were included and divided into the normal group (C group), NAFLD model group (M group), low-dose group, medium-dose group (T group), and high-dose group with intraperitoneal injection of arecoline. the expression of blood lipid level was significantly downregulated at all three concentrations of arecoline (p<0.05). alpha-diversity analysis of the intestinal flora showed significant differences among the three groups, with a significant reduction in population diversity in the M group and recovery of population diversity after arecoline treatment. at the phylum level, the relative abundance of Firmicutes was significantly higher in the T group and Proteobacteria in the M group. KEGG metabolic pathways were polyketide sugar unit biosynthesis and hypertrophic cardiomyopathy (HCM). 33 significantly different metabolites were revealed between three groups. Significantly different metabolites between the T and M groups included indolepyruvate, 2-deoxystreptamine, sakuranetin, glycyl-leucine, and riboflavin. KEGG metabolic pathway suggested a potential role for arachidonic acid metabolism, serotonergic synapse, neuroactive ligand-receptor interaction, tyrosine metabolism, and regiomelanin. Vitamin digestion and absorption as well as regulation of lipolysis in adipocytes were the main metabolic pathways that distinguished the T vs M group. PGE2 is involved in several metabolic pathways. Correlation analysis showed that 29 bacterial species were significantly associated with PGE2 in the M and T groups. Vagococcus, Lawsonia, Christensenella, unidentified Erysipelotrichaceae, unidentified Coriobacteriaceae, and five other bacterial groups were unique in the PGE2 metabolic pathway regulated by arecoline. Arecoline has lipid-lowering effects and may exert therapeutic effects in NAFLD through intestinal metabolites and intestinal flora as well as the Butyricicoccus/Christensenella/Coriobacteriaceae-COX2/PGE2 pathway. Thus, arecoline may represent a potential drug or target for the treatment of NAFLD.